2021
DOI: 10.37036/ahnj.v6i2.180
|View full text |Cite
|
Sign up to set email alerts
|

Pemberian Minuman Jahe Terhadap Tekanan Darah Penderita Hipertensi Di Posyandu Lansia Surya Kencana Bulak Jaya Surabaya

Abstract: Hypertension is a major modifiable risk factor to prevent cardiovascular disease and death, especially in the elderly. The increase in blood pressure in the elderly is affected by the loss of elastic tissue in the arteries and a concomitant increase in arterial stiffness. Management of hypertension is making lifestyle changes by limiting alcohol and sodium consumption, quitting smoking, increasing physical activity and adjusting diet. The therapy that will be used is ginger drink therapy. The aim of the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Blood pressure in the systole decreased while in the diastole blood pressure did not experience significant changes. Kritiani's research (2018) [5]. found the results of the influence before and after giving elderly exercise on the blood pressure of hypertensive patients after elderly exercise was carried out 3 times a week within 40 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Blood pressure in the systole decreased while in the diastole blood pressure did not experience significant changes. Kritiani's research (2018) [5]. found the results of the influence before and after giving elderly exercise on the blood pressure of hypertensive patients after elderly exercise was carried out 3 times a week within 40 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…(Solihin et al, 2020).. Kristiani and Dewi's research in 2018 showed that there was an effect before and after giving elderly gymnastics on the blood pressure of hypertensive patients after doing elderly gymnastics 3 times a week for 40 minutes. (Kristiani & Dewi, 2021).…”
mentioning
confidence: 99%
“…Gambar 15. Jahe Berdasarkan data dari Tabel 18 dan Gambar 15 dapat dilihat menurut penelitian yang dilakukan oleh(Kristiani, R. B., & Ningrum, S. S., 2021) didapatkan hasil setelah dilakukannya intervensi air jahe terdapat perbedaan tekanan darah yang ditunjukan dari tes Mann Whitney U menunjukan perbedaan tekanan darah 0.001 < 0.05 Mann Whitney U memiliki p-value 0.001 (<0.5) dari data diatas dapat disimpulkan jika mengkonsumsi air jahe berpengaruh terhadap penurunan tekanan darah lansia yang menderita hipertensi.…”
unclassified